The single-dose Janssen Ad26.COV2.S COVID-19 vaccine elicited robust and persistent anti-spike IgG antibody responses in a 12-month Ugandan cohort - Serwanga, Jennifer; Kato, Laban; Oluka, Gerald Kevin; Ankunda, Violet; Sembera, Jackson; Baine, Claire; Kitabye, Isaac; Namuyanja, Angela; Opio, Solomon; Katende, Joseph Ssebwana; Ejou, Peter, The COVID-19 Immunoprofiling Team; et al. (Frontiers in Immunology, 2024)
Introduction The study investigation examined the immune response to the Janssen Ad26.COV2.S COVID-19 vaccine within a Ugandan cohort, specifically targeting antibodies directed against spike (S) and nucleocapsid (N) proteins. We aimed to examine the durability and robustness of the induced antibody response while also assessing occurrences of breakthrough infections and previous anti-Spike seropositivity to SARS-CoV-2. Methods The study included 319 specimens collected over 12 months from 60 vaccinees aged 18 to 64. Binding antibodies were quantified using a validated ELISA method to measure SARS-CoV-2-specific IgG, IgM, and IgA levels against the S and N proteins. Results The results showed that baseline seropositivity for S-IgG was high at 67%, increasing to 98% by day 14 and consistently stayed above 95% for up to 12 months. However, S-IgM responses remained suboptimal. A raised S-IgA seropositivity rate was seen that doubled from 40% at baseline to 86% just two weeks following the initial vaccine dose, indicating sustained and robust peripheral immunity. An increase in N-IgG levels at nine months post-vaccination suggested breakthrough infections in eight cases. Baseline cross-reactivity influenced spike-directed antibody responses, with individuals harbouring S-IgG antibodies showing notably higher responses. Discussion Robust and long lasting vaccine and infection-induced immune responses were observed, with significant implications for regions where administering subsequent doses poses logistical challenges.